The proximity-concentration trade-off in a dynamic framework - Erdal Yalcin (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2007)
This paper presents a dynamic framework which implements risk as a continuous variable into the proximity-concentration trade-of concept. Additionally firms have the possibility to postpone their investment decision which gives them the possibility to collect further information about the volatile variable over time. On the basis of the real option theory (Dixit and Pindyck, 1994) an investment plan under uncertainty is derived. In contrast to static models firms postpone their investment decision although positive returns can be achieved. For specific risk values the model predicts, in the presence of a foreign direct investment choice, the export strategy can be rejected although it is dominating the FDI project and although it is worthier than its option value. The results of the model undermine empirical findings which analyze the impact of continuous variables on export and FDI patterns.
urn:nbn:de:bsz:21-opus-30601
Keywords: D81; D92; F17; F21; F23; F31; 330; export; FDI; uncertainty; real option approach; Direktinvestition; Export; Entscheidung bei Unsicherheit; Realoption; Theorie